Análisis del flujo metabólico de los materiales de construcción en la Ciudad de Riobamba - Herrera Mancero, José Antonio (2019)
The Construction industry is an indicative of the development and growth of the Human settlements, Cities and countries of the world, this is so important that on the last years the construction industry represents the 6% of the gross domestic product on a global level and the 8.5% in Ecuador, The development of the societies goes hand to hand with the use of natural resources and the waste that this activity generates. The urban metabolism is the process of analyze and evaluation of the sustainability of the city that looks for the transformation of the industrial processes and to minimize the impacts on the environment caused for the use of natural resources and energy. The objective of the investigation is contributing with statistic data and generate the index of the metabolic flow for the modular units and stony materials for the use on concrete and mix mortar used on the construction of buildings in the city. The investigation was carried out through the inventory of urban construction permits approved by the GADM of Riobamba in the last 6 years, In order to know the volume of production of building materials, calculate the amount of material required by the buildings of the city and determine the volume of waste generated by the construction to plan or manage the city in the future and not compromise the development of future generations limiting natural resources or raw materials.